An ergonomic analysis of a closed circuit television rear vision system for forestry machine operators : a thesis in partial fulfilment of the requirements for the degree of Master of Ergonomics at Massey University - Parker, Richard John (Massey University, 2003)
The Bell Logger is a fast highly mobile forestry machine used in close proximity to workers on foot. It can, along with other machines, inadvertently collide with workers, other machines or logs which subsequently hit workers. To date the only successful way to prevent injury to workers on foot is to completely remove them from the work area of the Bell Logger. This is often operationally difficult and does not prevent collisions between machines or other objects. One potential solution is to improve the rear vision of the machine operator. A literature search was carried out to review information on human vision, issues of driver vision from vehicles, epidemiology of forestry injury related to mobile machines, methods of assessing vision from vehicles and existing rear-view aids for vehicle drivers. A questionnaire was used to gather information from Bell Logger operators on their opinion of the rear view camera system. Video records of Bell Logger movements and operator head glance direction were analysed to characterise the operating environment and style without and with the rear view camera system. Mobile machine related injuries on the skid site are a significant problem resulting in 1304 lost work days in the period 1995 to 2002. The normal operational environment of the Bell logger operator is characterised by frequent machine changes in direction (eight to 10 per minute) and frequent head movements (four to five per minute) to see if the way is clear. Results indicate that the rear vision camera system appears to have potential as a valuable addition to the Bell Logger operating under typical New Zealand forestry conditions, and it resulted in a 20% increase in Bell Logger activity.
Appendix 7 Reports removed due to copyright. Can be read from the original copy held in the library.
Keywords: Logging Machinery; Safety measures; Closed-circuit television